Knowledge Improvement through Smartphone Utilization in the Remote Control System Module of Electronic Equipment at SMKS Muhammadiyah 9 Medan - Abdullah; Maharani Putri; Moh. Zainul Haq; Arridina Susan Silitonga; Cholish; Suprianto; Nooritawati Md Tahir; Abdul Rahim Bin Ridzuan; Pius Fernando Hutauruk; Priansus Rhein Rumahorbo (CERED Indonesia Publishing, 2023)
Control technology is currently growing rapidly, one of the utilization of control technology that is currently experiencing rapid development is control of smart homes and automation systems coupled with rapid advances in the field of the Internet of Things, so that control technology becomes a remote control concept that is widely applied. Thematic Community Service Collaboration (TCSC) activity is a series of community service activities intended for the downstreaming of research products of Medan State Polytechnic lecturers in collaboration with Universiti Teknologi MARA (Malaysia) lecturers that can be utilized by the community (partner), namely SMKS Muhammadiyah 9 Medan aims to provide training from modules / trainers that have been specially designed consisting of several electronic equipment that has been equipped with wireless communication so that students can control electronic equipment remotely only through an application from a Smartphone without having to make direct contact like using a mechanical switch in general. The method used in this service is the lecture method followed by the discussion and question and answer method followed by the module / trainer demonstration method and how it works and the direct interaction method, namely students can try or practice directly, so that this training increases students' knowledge, skills and creativity towards the development of remote control technology in the future.